Business angels: a research review and new agenda. Issue 3 (3rd July 2017) - White, Brett A.; Dumay, John
Abstract: This paper provides a structured literature review of 84 business angel articles published between 2000 and 2013, building on the 1999 review contacted by Mason and Harrison. The articles are classified according to the generational framework laid out by Mason and Harrison, which describes first and second generations of articles (prior to 1999) and calls for a third generation of research. We find that Mason and Harrison's agenda has largely been met, with some notable gaps. We also find that the research is diverse, with many articles falling into what Mason and Harrison call first and second generations. Our paper outlines a new agenda for research focusing on six key areas. Finally, we conclude with a discussion of key implications for policy and practice.